A Young Patient with Coronary Artery Disease: Fortuity or Regularity? - Gogayeva, Olena K.; Heneha, Mariia B. (Ukrainian Journal of Cardiovascular Surgery, 2024)
The aim. To analyze the reasons for hospitalization of young patients in the department of surgical treatment of coronary artery disease and to identify risk factors for premature progression of atherosclerosis. Materials and methods. Retrospective analysis of data from patients younger than 45 years who were hospitalized in the department of surgical treatment of coronary artery disease of the National Amosov Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine in the period from September 2023 to September 2024. All the patients underwent standard clinical and laboratory examinations, electrocardiography, echocardiography, and coronary angiography, based on the results of which the heart team decided on further treatment tactics. Results. Among 1187 patients who were hospitalized in the department during the year, 78 (6.57%) were younger than 45 years (mean age 40.7 ± 4.04 years). The admission was elective in 57 (73.1%) patients and urgent in 21 (26.9%) patients. During coronary angiography, hemodynamically significant lesions of the coronary arteries were detected in 45 (57.7%) patients, moderate (up to 50%) lesions of the coronary arteries in 22 (28.2%), intramural course of the left anterior descending artery in 6 (7.7%), and in 5 (6.4%) cases, coronary lesions were not detected. Coronary artery stenting was performed in 27 (60%) patients, coronary artery bypass grafting in 12 (26.6%) patients, which in 3 (25%) cases was supplemented by left ventricular aneurysm resection; myocardial revascularization was delayed in 6 (13.3%) patients. Conclusions. The frequency of hospitalization of patients younger than 45 years with suspected coronary artery disease is 6.57%, among which cardiac surgery is required in 57.7%. Among the factors of premature progression of atherosclerosis of the coronary arteries, the role of diabetes mellitus (p = 0.0440), long-term smoking experience of 20.7 ± 7.9 years (p = 0.0002) and history of cerebral blood circulation disorders (p = 0.0478) was proven.